Dosis de dos abonos orgánicos y su efecto en el rendimiento del forraje Morus nigra L. “morera” en Zungarococha Perú – 2021 - Acho Pizango, Ruben (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy, entitled DOSE OF TWO ORGANIC FERTILIZERS AND ITS EFFECT ON FORAGE YIELD Morus nigra L. “Morera” IN ZUNGAROCOCHA PERU – 2021. With a Design of Complete Random Blocks (D.B.C.A), with five treatments and four repetitions, the treatments under study were: T0 (control) T1 (10 tons of compost), T2 (20 tons of compost), T3 (10 tons of beef) and T4 (20 tons of beef): obtaining the following results That, for the plant height variable, no significant statistical difference was found (p > 0.05) between the five doses of organic fertilizers, where treatment T2 (40 tons of compost/ ha) obtained 1.69 meters. With T2 (40 tons of compost/ha), higher yields in green matter and dry matter (kg/m2) of 2.89 kg/m2 and 0.61 kg/m2 were achieved. With T2 (40 tons of compost/ha), a plant coverage percentage of 95.77% was achieved. With T2 (40 tons of compost/ha), 0.81 kilos/m2 were achieved in leaves and 2.08 kilos/m2 in stems, this indicates that the greatest weight occurs in the tender branches. With T2 (40 tons of compost/ha), green matter yields of 28,925 kg/ha were achieved 60 days after sowing.